Muslim women adhering to Minangkabau’s bajapuik tradition in Cirebon, West Java: compromizing a gendered culture in Islamic law - Wardah Nuroniyah; Bani Syarif Maula (State Institute of Islamic Studies (IAIN) Salatiga, 2022)
Bajapuik refers to a customary engagement (khiṭbah) of the Minangkabau Pariaman community, where the prospective bride’s family gives a certain amount of money (japuik) to the groom’s family prior to a marriage. Islamic law allows a person to give a certain amount of money or gifts in the process of engagement. However, when the engagement is revoked and the marriage fails, the status of the money given during the engagement has been much contested. This study aims to explore and understand the positive relationship between Islamic law in the bajapuik tradition and local traditions. This study focuses on the legal aspects of engagement in the bajapuik tradition viewed from Islamic law and gender analysis. A descriptive qualitative approach was adopted with the primary data obtained through interviews. Data analysis was carried out using a legal approach, a sociological approach, and a philosophical approach. This study concludes that the bajapuik tradition depicts women as having a higher position than men. For the Pariaman community in Cirebon, the annulment of an engagement (khiṭbah) is a disgrace to tradition. An engagement is considered as a legally binding contract. In other words, customary provisions have coercive power to bounded communities. If an engagement is revoked without a valid reason, the responsible person can be sued for breaking the contract with certain compensations. Morevover, when a dispute occurs over property or finances, Minangkabau customary law allows the aggrieved party to take action against the khiṭbah violators in the form of returning property or money.